INCREASING MULTICULTURAL AWARENESS THROUGH EXPERIENTIAL LEARNING MODEL - Eny Usmawati (Universitas Pendidikan Indonesia, 2022)
This study aims to increase multicultural awareness in the effectivenessofthe Experiential Learning model in multicultural group students (Javanese and Chinese tribes) at SMP 1 Negeri Parung Bogor . Within group or individual design and equivalent materials design were the designs in this study. Meanwhile, the data collection instrument in this study uses a multicultural awareness scale, to increase multicultural awareness of experiential learning model learners as an instrument in this research. Uji nonparametric statistics and visual data analysis is a data analysis in this study to see changes in multicultural awareness. Increasing multicultural awareness of multicultural group students (Javanese and Chinese tribes) at SMP Negeri 1 Parung Bogor in using model Experiential Learning effectively.